Necrosis of maxilla, nasal, and frontal bone secondary to extensive rhino-cerebral mucormycosis - Verma, Ajay (Medknow Publications & Media Pvt Ltd, 2013)
Mucormycosis is an opportunistic fulminant fungal infection caused by zygomycetes. This fungus can cause a variety of infections in human beings, particularly in the uncontrolled diabetes mellitus. Zygomycetes impinge into the vascular network, resulting in thrombosis and necrosis of the surrounding hard and soft tissues. The infection begins in the nose and paranasal sinuses due to inhalation of fungal spores and spread to orbital and intracranial structures either by direct invasion or through the blood vessels. Sinus mucormycosis is often accompanied by a poor prognosis and a high mortality rate. Hence, aggressive surgical intervention with antifungal therapy is usually necessary. Early diagnosis and prompt treatment can reduce the mortality and morbidity of this lethal fungal infection. We report a case of aggressive rhino-cerebral mucormycosis in a 58-year-old female patient with uncontrolled diabetes mellitus.